13) Here, Sequence : -2, -6, -18, -54
Common Ratio = a₂/a₁ = -6/-2 = 3
As the expression is in negative sign, it's sequence will be -3ˣ
Where x = number of terms in the sequence [ By this rule, you can calculate the unknown nth number]
In short, Option C is your answer!!!!
14) Here, a₂-a₁ = 6-2=4, a₃-a₂ = 12-6 = 6
So, difference is increasing by 2 at each step, as it's not arithmetic, It must deviate by the square on it. As only one option has square on it, it will be
(n²+n)
In short, Option B is your final answer.
15)V = 2πr²h
h = V / 2πr²
In short, Option D is your final answer.
Hope it helped, Please Let me know, if you have some doubts!!